Cracking Ray Tubes: Reanimating Analog Video in a Digital Context. - Connolly, James; Evans, Kyle (Leonardo Music Journal, 2014)
This paper investigates the aesthetic potentials of analog and digital hybridized systems to generate genuinely new sonic and visual experiences. The authors discuss their use of the cathode ray tube as a technological and cultural platform for real-time performance in the context of digital screen culture and the digital glitch.